Solving delay differential equations (DDEs) using nakashima's 2 stages 4th order Pseudo-Runge-Kutta method - Ayunni Sarbi N.A.; Bin Mamat M.B. (2013)
This paper is investigate numerically the problem on solving Delay Differential Equations (DDEs) using Nakashima’s 2 Stages 4th Order Pseudo-Runge-Kutta Method and also developed the algorithm of Nakashima’s 2 Stages 4th Order Pseudo-Runge-Kutta Method incorporates with Hermite Interpolation. Numerical result is applied to a real life problem which is Food-Limited Model. Mathematica 7 software and Microsoft Excel are used to develop the calculation